PERAN MANAJERIAL KEPALA SEKOLAH DALAM MENGOPTIMALKAN PENGEMBANGAN KARAKTER SISWA DI SMP FRATER DON BOSCO MANADO PADA ERA KURIKULUM MERDEKA - Mokalu, Yohanes Bery; Rofinus, Banunaek; Sendiang, Dhea Jessica; Kondoy, Eric; Arundaa, Rillya; Pangalila, Theodorus; Umbase, Ruth Sriana (Jurnal Manajemen Pendidikan, 2026)
This study aims to analyze the principal’s management in developing students’ character at SMP Don Bosco Manado based on the Merdeka Curriculum. The study focuses on how the principal plans, implements, and evaluates character development programs, as well as the supporting and inhibiting factors in their implementation. This research employs a qualitative descriptive method with a case study approach. Data were collected through in-depth interviews, participatory observation, and documentation. The results indicate that the principal has effectively applied management based on the Merdeka Curriculum through program planning, teacher development, and student activity evaluation. The character development programs have successfully enhanced students’ discipline, responsibility, teamwork, and religious attitude. Supporting factors include teacher support, school facilities, and student participation, while inhibiting factors include limited time and external environmental influences. In conclusion, the principal’s role is strategic in shaping students’ character, and effective management positively impacts the implementation of the Merdeka Curriculum.